Risk factors linked to surgical site infections: a prospective survey on an Albanian population following abdominal surgery - Kaçani, Ardit; Lilaj, Krenar; Shpata, Vjollca; Mulgeci, Fjoralba; Ferizaj, Sara; Xure, Irisi; Sulku, Emigleo; Durro, Vjollca (The Journal of Infection in Developing Countries, 2026)
Introduction: Despite global improvements in perioperative care, surgical site infections (SSIs) continue to pose a significant burden, and data from Albania remain limited. This study aimed to determine the incidence of SSIs following abdominal surgery in an Albanian tertiary hospital and identify associated risk factors, microbiological profiles, and antimicrobial resistance patterns. Methodology: A prospective observational study was conducted at the University Hospital Centre “Mother Theresa” in Tirana. A univariate and multivariate logistic regression adjusted for confounders was performed to identify factors associated with the development of SSIs. Results: 1179 patients were enrolled in the study, with a mean age of 57.80 ± 16.16 years (range, 19-92 years), and 51.23% were male. 64 patients (5.43%) developed surgical site infections following abdominal surgery. The most frequently isolated microorganisms from infected surgical wounds were Escherichia coli and Enterococcus faecalis, identified in 39.0% and 22.0% of cases, respectively. The rate of SSIs was higher in patients undergoing lower gastrointestinal surgery compared to those having upper gastrointestinal procedures. As risk factors for developing SSIs in univariate regression analysis, age ≥ 50 years (OR: 2.69, 95% CI: 1.25–5.78), comorbidities (OR: 2.71, 95% CI: 1.53–4.83), and type 2 diabetes mellitus (OR: 2.98, 95% CI: 1.59-5.56) were identified. Conclusions: Although the rate of SSIs after abdominal surgery has decreased, it remains a significant concern in Albania. Age, comorbidities, and lower gastrointestinal surgery are important risk factors. The findings emphasise the need for improved infection control and antimicrobial stewardship to reduce postoperative complications.